2017
DOI: 10.1073/pnas.1612881114
|View full text |Cite
|
Sign up to set email alerts
|

Biological origins of color categorization

Abstract: The biological basis of the commonality in color lexicons across languages has been hotly debated for decades. Prior evidence that infants categorize color could provide support for the hypothesis that color categorization systems are not purely constructed by communication and culture. Here, we investigate the relationship between infants' categorization of color and the commonality across color lexicons, and the potential biological origin of infant color categories. We systematically mapped infants' categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 60 publications
4
72
0
1
Order By: Relevance
“…On one hand, it has been established that children perceive the color spectrum categorically, well before they start to show signs of understanding color words (Bornstein, 1985b;Franklin & Davies, 2004;Skelton, Catchpole, Abbott, Bosten, & Franklin, 2017;Yang, Kanazawa, Yamaguchi, & Kuriki, 2016). The color lexicon is theoretically interesting in many respects, but particularly so when considering the relation between pre-linguistic perception and language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, it has been established that children perceive the color spectrum categorically, well before they start to show signs of understanding color words (Bornstein, 1985b;Franklin & Davies, 2004;Skelton, Catchpole, Abbott, Bosten, & Franklin, 2017;Yang, Kanazawa, Yamaguchi, & Kuriki, 2016). The color lexicon is theoretically interesting in many respects, but particularly so when considering the relation between pre-linguistic perception and language.…”
Section: Introductionmentioning
confidence: 99%
“…The color lexicon is theoretically interesting in many respects, but particularly so when considering the relation between pre-linguistic perception and language. On one hand, it has been established that children perceive the color spectrum categorically, well before they start to show signs of understanding color words (Bornstein, 1985b;Franklin & Davies, 2004;Skelton, Catchpole, Abbott, Bosten, & Franklin, 2017;Yang, Kanazawa, Yamaguchi, & Kuriki, 2016). The fact that infants perceive the color spectrum as distinctive color categories may be taken to mean that they only need to learn the word form for each of the pre-segmented categories (e.g., Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…And, while acknowledging that linguistic criteria may be of importance in classifying colours in terms of language, we believe that the classification according to colour categories is not dependent upon language and experience. Supporting evidence for this comes from the ability of children and monkeys to categorize colours much like adult humans (Sandell, Gross, & Bornstein, ; Skelton, Catchpole, Abbott, Bosten, & Franklin, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to discriminate colors progressively improves through development until adolescence (Knoblauch, Vital‐Durand, & Barbur, ). Previous studies have shown that infants look longer at some colors than others (e.g., Franklin, Bevis, Ling, & Hurlbert, ; Franklin et al., ; Zemach, Chang, & Teller, ) and can categorize the spectrum of color (e.g., Skelton, Catchpole, Abbott, & Franklin, ). However, we know little about how the dimensions of color contribute and interact in infants’ perception of color.…”
Section: Perceptual Salience Of Physical Dimensionsmentioning
confidence: 99%